2020
DOI: 10.1093/eurheartj/ehaa423
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin–aldosterone system dysregulation and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection

Abstract: high-risk population as well as a group of individuals with a dysregulated RAAS in favour of an ACE/angiotensin II signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…We observed that some researchers interpreted that the use of ACEI/ARB in COVID-19 disease, and the upregulation ACE2 mRNA expression (using ACEI/ARB) levels found by Ferrario et al [42••], attributed a protective role that could reduce lung injury by leading away from Ang II (which is responsible for lung injury) to the pathway ACE2-Ang (1-7) [51,56]. For the benefit of those who may have missed the point, we wish to reiterate that Ferrario et al carried out their research in normal rats, which were not hypertensive, or having other cardiac diseases, diabetes mellitus or malignancies, nor were they being treated with either ACEIs or ARBs for any of the said abnormalities.…”
Section: Effects Of Animal Models On Sars-cov-2 Infection In Humansmentioning
confidence: 79%
“…We observed that some researchers interpreted that the use of ACEI/ARB in COVID-19 disease, and the upregulation ACE2 mRNA expression (using ACEI/ARB) levels found by Ferrario et al [42••], attributed a protective role that could reduce lung injury by leading away from Ang II (which is responsible for lung injury) to the pathway ACE2-Ang (1-7) [51,56]. For the benefit of those who may have missed the point, we wish to reiterate that Ferrario et al carried out their research in normal rats, which were not hypertensive, or having other cardiac diseases, diabetes mellitus or malignancies, nor were they being treated with either ACEIs or ARBs for any of the said abnormalities.…”
Section: Effects Of Animal Models On Sars-cov-2 Infection In Humansmentioning
confidence: 79%
“…Zhang et al found that the mortality of COVID-19 sufferers treated with ACEIs/ARBs was much lower than those treated without ACEIs/ARBs [117]. Several clinical trials have also demonstrated that the up-regulation ACE2 expression levels induced by ARBs and ACEIs are supposed to reduce lung injury in SARS-CoV-2 infection presumably via decreasing ACE-derived Ang II [118,119]. While several organizations have issued statements advising the continuation of treatment of COVID-19 with ACEIs/ARBs, more large-scale clinical studies are still warranted to elucidate whether it could be associated with other unknown damages to the human body [120].…”
Section: Aceis/arbsmentioning
confidence: 99%
“…However, the virus has also been shown to affect the ocular system ( Wu et al, 2020 ), the gastrointestinal system ( Redd et al, 2020 ), the musculoskeletal system ( Cipollaro et al, 2020 ), the skin ( Casas et al, 2020 ), and the cardiovascular system ( Nishiga et al, 2020 ). There are numerous pathological mechanisms that are potentially involved in these forms of injury, including direct viral toxicity ( Gupta et al, 2020 ), immune dysregulation ( Acharya et al, 2020 ), endothelial derangement ( Nizzoli et al, 2020 ), and an imbalance in the renin angiotensin aldosterone system ( John et al, 2020 ). Given the complexity of the mechanisms involved, it is vital that we develop novel therapies against the SARS-CoV-2 virus that are novel, safe and effective.…”
Section: Introductionmentioning
confidence: 99%